Date-derived industries: A review of common products, manufacturing methods, and leading countries - Abdullah AlFaris, Nora; Zaidan AlTamim, Jozaa; Abdulaziz AlMousa, Lujain; Ali AlGhamidi, Fatima; Abdullah Albarid, Najla (Emirates Journal of Food and Agriculture, 2022)
The date fruit, a nourishing food appreciated worldwide, plays an important role in producing countries’ economic and political aspects. Date palms provide numerous products, including date syrup, alcohol, vinegar, date powder, and sugar. This review was undertaken to summarize information about the common date-derived products, the manufacturing methods used, and the leading countries in the date-derived industry. Additionally, the review highlights the future challenges in developing the date industry. The difficulties that accompanied the preparation of this review included the scarcity of modern and reliable information, especially the statistics related to date-derived products from leading countries involved in this industry. This may be due to the incompleteness of such information or the lack of interest in publishing them in reliable scientific sources.